Evaluation of the Efficiency of Al-Dhibai Wastewater Treatment Plant in Salah Al-Din Governorate - Saleh, Dr. Mowafaq Inhab; Mohammed, Buraq Salah (Journal of Science in Medicine and Life, 2025)
The Al-Dhibai wastewater treatment plant in Tikrit City, Salah Al-Din Governorate, was evaluated from March to August 2024. The study assessed environmental pollution parameters for both influent and effluent water, including biochemical oxygen demand (BOD5), chemical oxygen demand (COD), total suspended solids (TSS), total dissolved solids (TDS), pH, phosphate concentration (PO₄), nitrate concentration (NO₃), chlorides (Cl⁻), and the concentration of certain heavy metals such as lead (Pb), cadmium (Cd), and zinc (Zn). The plant's efficiency in removing pollutants was found to be 55.29% for BOD5, 74.26% for COD, and 79.54% for TSS. The plant's design capacity is 20,000 m³/day, with an available capacity of 20,000 m³/day. The incoming wastewater volume is approximately 12,000 m³/day, while the treated water output ranges between 8,000 and 10,000 m³/day.